Exploration of potential geothermal fields using GIS-based entropy method: A case study of the Sandikli - Yalcin, Mustafa; Kalaycioglu, Samet; Basaran, Can; Sari, Fatih; Gul, Fatmagul Kilic (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Geothermal energy has great potential among Turkey's sustainable energy sources. Especially the western regions of our country are the regions where these sources are intensified. The study area, Sand & imath;kl & imath; district, is one of the regions in the west of Turkey with high geothermal energy. In the study, potential geothermal fields are tried to be explored in Sand & imath;kl & imath;. Drainage density, slope, proximity to faults, geological indicators, and land surface temperature (LST) anomaly used to determine the geothermal potential of the study area based on literature research and experts' opinions. Within the scope of multi-criteria decision analysis (MCDA), a geothermal favorability map is created by synthesizing the layers formed with the weights that are calculated with the Entropy Method. The results of the Entrophy method compared with the AHP results for evaluating the consistency and presicion of the results. It has seen that same potential geothermal areas were detected from both methods. Besides, the Entrophy results were more sharper and had higher sensibilities. As a results of the study, Kusura, & Ccedil;ak & imath;r, Ko & ccedil;hisar, Bas,kuyucak, and Ekinhisar, extremly high geothermal potential regions were proposed as new geothermal fields in the Sand & imath;kl & imath; province.
Keywords: Geographic information systems (GIS); Multi-criteria decision analysis(MCDA); Entropy method; Geothermal exploration; WESTERN ANATOLIA; SYSTEM; MODEL; INTEGRATION; TECHNOLOGY; RESOURCES; MOUNTAIN; GRABEN; AKITA; Science & Technology - Other Topics; Energy & Fuels